PROFIL PENGELOLAAN OBAT DI RUMAH SAKIT DAERAH IDAMAN BANJARBARU - Noor Aisyah; Rizkiyah; Fitrah Safran Ilahi; Ayu Soraya (Jurnal Insan Farmasi Indonesia, 2022)
Effective drug management is carried out to prevent drug shortages, drug excess which causes the drug to reach the expiration date. The purpose of this study was to determine the percentage of drug planning accuracy, the frequency of drug procurement, the percentage of damaged and expired drugs, and the percentage of dead stock of drugs at Idaman Hospital Banjarbaru. This research was conducted with a descriptive, non-experimental observational design. The data taken is retrospective data, then analyzed quantitatively and the data is presented descriptively. The results of this study show that the value of planning achievement in a period of 2021 is still not according to the indicator standard, which is 94.725%. The frequency of procurement of each drug item in 2021 out of 204 drug items taken randomly, there are 199 drug items that are classified as low and 5 drug items that are classified as moderate. The percentage value of expired and damaged drugs is quite good, namely 0.04% with a loss of Rp.7,894,034 during the 2021 period from the standard indicator value <1%. The percentage value of dead stock still does not match the standard value. Drugs that are not transactions for 3 months are 2.80%.